Impact of Sarcopenia on Survival and Clinical Outcomes in Patients With Liver Cirrhosis - Topan, Mirabela-Madalina; Sporea, Ioan; Dănilă, Mirela; Popescu, Alina; Ghiuchici, Ana-Maria; Lupuşoru, Raluca; Şirli, Roxana (Frontiers in Nutrition, 2021)
Background: Sarcopenia is now recognized more and more as a biomarker with poor outcomes in cirrhotic patients. Aims: The purpose of this study was to investigate the prevalence of sarcopenia in patients with liver cirrhosis and prospectively investigate the association between sarcopenia and different complications and its impact on survival. Material and methods: This prospective study included patients with liver cirrhosis admitted to our department from 2018 to 2020. Sarcopenia was assessed according to EWGSOP2 criteria, incorporating low Handgrip strength (<27 kg for men and < 16 kg for women) with low skeletal muscle index evaluated by CT (<50 for men and <39 for women). Associations between sarcopenia and portal hypertension-related complications, infectious complications, and risk of hepatocellular carcinoma, the number of in-hospital days, thirty-day readmission, and survival over the next 6 and 12 months were analyzed. Results: A total of 201 patients were enrolled in the study, 63.2 % male, mean age 61.65 ± 9.49 years, 79.6% Child-Pugh class B and C. The primary etiology of liver cirrhosis was alcohol consumption (55.2%). The prevalence of sarcopenia was 57.2 %, with no significant differences between the male and female groups. Significant associations were found between sarcopenia and portal hypertension-related complications, infectious complications, and risk of hepatocellular carcinoma. In multivariate analysis, sarcopenia was assessed as a risk factor alone, increasing the risk for ascites 3.78 times, hepatocellular carcinoma by 9.23 times, urinary tract infection by 4.83 times, and spontaneous peritonitis 2.49 times. Sarcopenia was associated with more extended hospital stay and higher 30 days readmission. Six months and 1-year survival were reduced in the sarcopenia group than in the non-sarcopenia group (p<0.0001). Conclusion: Sarcopenia is a common complication of liver cirrhosis and associates with adverse health-related outcomes and poor survival rates.